The Action of Efflux Pump Genes in Conferring Drug Resistance to Klebsiella Species and Their Inhibition - Ashwath, Priyanka; Sannejal, Akhila Dharnappa (Journal of Health and Allied Sciences NU, 2021)
Nosocomial infections caused by Klebsiella species are characterized by high rates of morbidity and mortality. The emergence of the multidrug-resistant (MDR) and extensive drug-resistant (XDR) Gram-negative bacteria reduces the antibiotic efficacy in the treatment of infections caused by the microorganisms. Management of these infections is often difficult, due to the high frequency of strains resistant to multiple antimicrobial agents. Multidrug efflux pumps play a major role as a mechanism of antimicrobial resistance in Gram-negative pathogens. Efflux systems are significant in conferring intrinsic and acquired resistance to the bacteria. The emergence of increasing drug resistance among Klebsiella pneumoniae nosocomial isolates has limited the therapeutic options for treatment of these infections and hence there is a constant quest for an alternative. In this review, we discuss various resistance mechanisms, focusing on efflux pumps and related genes in conferring resistance to Klebsiella. The role of various efflux pump inhibitors (EPIs) in restoring the antibacterial activity has also been discussed. In specific, antisense oligonucleotides as alternative therapeutics in combatting efflux-mediated resistance in Klebsiella species have focused upon.
Keywords: efflux pump systems; K. pneumoniae; efflux pump inhibitors; antisense oligonucleotides